Optimizing Effort to Quell The Crime of Violence in The Perspective of A Criminal Policy Approach - Imam Ramadhani (Journal of Social Science, 2022)
There are three objectives to be achieved in this research, namely; the first examines and analyzes efforts to overcome the crime of theft with violence in the perspective of a criminal policy approach, the second examines and analyzes the factors that encourage and cause criminal acts of theft with violence in Indonesia. Violence is going well in Indonesia. With Problem Formulation 1. How are the efforts to tackle the crime of theft with violence in the perspective of a criminal policy approach? 2. What factors encourage criminal acts of theft with violence to occur in Indonesia?. 3. How does the ideal policy in efforts to overcome the crime of theft with violence work well in Indonesia? This study uses a qualitative method with descriptive-analytical research specifications that describe the legislation. The stages of the research were carried out in two stages: library research and field research. Drawing conclusions from the study results was carried out by providing conclusions on data analysis which included searching for meaning and providing explanations from the data that had been obtained. The results of this study indicate; first, efforts to overcome violent crimes by increasing the effectiveness of the Extralegal system or informal system and preventive efforts including patrols, socialization, and streamlining the role of the environmental security system as well as providing training in the field of IT and repressive mapping, recording, and monitoring the network against the perpetrators/prisoners who have been arrested & sentenced to the second, the factors that encourage perpetrators of violent criminal acts are economic factors, education, negligence of the victim, the environment and the weakness of repressive measures. An inter-agency Coordinating Minister and a Government Committee are formed, chaired by the Minister of Home Affairs. Policies at the Polres, such as the Serang City Police, carry out firm and measurable action in arrests; in Karawang, they have the Life360 application and carry out KRYD (improved routine activities).